Starch-cellulose composites with controlled crystallinity: towards the better understanding of structural features and enzymatic hydrolysis. - Diaz - Calderon; Paulo (2023)
RESULTADOS OBTENIDOS: Describa los resultados obtenidos de su investigación haciendo referencia a los objetivos originales y/o previamente modificados de su propuesta. La extensión máxima de esta sección es de 5 páginas (letra tamaño 10, Arial o Verdana). El proyecto 1191375 tenía como Objetivo General: Evaluate the effect of cellulose nanocrystals (CNC) on retrogradation kinetic of starch with different amylose content and crystalline polymorphisms and its effect on accessibility for in-vitro gastric enzymatic hydrolysis. Para ello se plantearon los siguientes Objetivos Específicos: o Chemical and physical characterization of starches and CNC considering composition, topography and morphological features, granule size distribution, surface electrical charge and crystallinity. o Analyse the effect of CNC on the gelatinization of different starches evaluating the changes in viscoelasticity, thermal properties, birefringence and pasting properties. o Evaluate the effect of CNC on the retrogradation kinetic of different starches in terms of viscoelasticity, mechanical and thermal properties, crystallinity, molecular mobility and molecular order. o Kinetic of retrogradation of starches determined by the Avrami model. o Analyse the effect of CNC on the crystalline configuration of retrograded starches at different molecular scales (macro, meso and micro). o Evaluate the crystalline configuration of CNC-retrograded starches by gastric enzymatic hydrolysis in-vitro level. Las actividades que permitieron dar cumplimiento total o parcial a cada uno de los objetivos se describen a continuación: 1. Chemical and physical characterization of starches and CNC considering composition, topography and morphological features, granule size distribution, surface electrical charge and crystallinity. Análisis de composición proximal de los distintos almidones (papa, trigo y waxy) mostraron, como era esperado, que estaban constituidos principalmente por carbohidratos (~99%) y cenizas (~1%), con un nivel no detectable de lípidos ...